The Influence Of Mental Health Conditions Of Indonesian Teenagers To Realize A Golden Indonesia 2045 - Meilva Farrah Dilla; M Khalid Al Aziz; Nazhifa Yasmin Amri; Nabira Mutiara; Miftahul Jannah (Jurnal Ekonomi, 2024)
The vision of "Golden Indonesia 2045" targets Indonesia as a developed country with superior human resources (HR) and global competitiveness. Adolescents, as the nation's next generation, play a central role in achieving this vision. However, their mental health faces serious challenges that can hinder their full potential. This study explores the influence of Indonesian adolescents' mental health conditions on their contribution to achieving national development goals by 2045. Factors such as social pressure, academic expectations, and the impact of social media play a significant role in influencing adolescent mental health. If left untreated, mental disorders can reduce productivity, innovation, and the quality of life of the younger generation, which can ultimately affect the achievement of Golden Indonesia 2045. This study emphasizes the importance of psychosocial support, inclusive education, and responsive policies to ensure adolescent mental well-being and support their strategic role in national development.